Injuries from firearm in ENT - Monteiro, Marta (2010)
The increase in urban violence leads to more patients in Emergency Rooms with lesions from firearms. The Health Professionals must be prepared for correct attendance to these cases.The authors present a bibliographical revision of injuries from firearm in Ear Nose and Throat (ENT), from diagnosis to therapy, based on several cases attended in the Emergency Room of ENT Department of the Garcia de Orta Hospital.The authors intend to point out the need of the ENT surgeon to be familiarized with the procedures in these cases, because the injuries in the face and neck can cause high morbidity and mortality, since there are multiple vital structures in these anatomical areas.